2020
DOI: 10.23937/2469-5823/1510144
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent the Hand Hygiene among Health Care Workers Become the Core of Best Practice in the COVID-19 Era?

Abstract: In the Era of COVID-19 outbreak, hand hygiene become a particularly critical for frontline healthcare workers (HCWs) who are overstretched and for whom this key routine task must be easy to complete and effective to prevent Healthcare-associated infections (HAIs). Therefore, this current study aims to assess the level of knowledge, attitude and practice of hand hygiene among the HCWs and the potential factors influencing hand hygiene (HH) compliance according to the hand hygiene protocols at primary health car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…The study results are similar previous studies (9) which indicated that providing facilities with clean water, soap, and hand rub, at various places increased hand washing practice. Similarly, previous research on access to knowledge and information about hand hygiene and covid-19 vaccines has presented similar ndings as highlighted by (10). The author's ndings revealed that participants who had received formal hand hygiene training applied the practice routinely during Covid-19.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The study results are similar previous studies (9) which indicated that providing facilities with clean water, soap, and hand rub, at various places increased hand washing practice. Similarly, previous research on access to knowledge and information about hand hygiene and covid-19 vaccines has presented similar ndings as highlighted by (10). The author's ndings revealed that participants who had received formal hand hygiene training applied the practice routinely during Covid-19.…”
Section: Discussionsupporting
confidence: 73%
“…In a study to assess hand hygiene compliance in India, the study ndings indicated that spreading out facilities with clean water, soap, basins, and hand rub enhanced the use of hand washing (9). Also, a study to assess hand hygiene practices among Health Care Workers in Riyadh, Saudi Arabia, the study results showed that the participants who had formal hand hygiene instruction used it regularly throughout Covid-19 (10). A study in Sub-Saharan Africa to investigate the obstacles to hand hygiene practices revealed that to improve hand hygiene practices, it was necessary to offer education on the topic and sustainable solutions to the water shortage, disinfectants, incentives, among other remedies (11).…”
Section: Introductionmentioning
confidence: 97%
“…Those with a good knowledge of hand hygiene were 3.45 times more likely to comply in this study than those with poor knowledge. This was confirmed by a study conducted in Saudi Arabia's Prince Sultan Military Medical City, which found that healthcare workers' knowledge was significantly associated with good hand hygiene compliance [ 32 ]. This could be linked to having a good understanding of hand hygiene compliance, which can help you comply with hand hygiene in the recommended manner, identify the benefits and drawbacks of hand hygiene compliance, and identify the route of healthcare-acquired infection transmission and how to avoid it.…”
Section: Discussionmentioning
confidence: 60%
“…We, therefore, recommend educating them on the importance of handwashing for at least 20 sec, as recommended by the WHO. Self-reported adherence to frequent ('usually') use of hand antisepsis using alcohol-based hand rub reached 72.5%, which was lower than the 94.8% reported by Al Mutairi et al (25). The major determinants of the use of alcohol-based hand rubs are the cost and availability of these products (25).…”
Section: Discussionmentioning
confidence: 87%
“…Self-reported adherence to frequent ('usually') use of hand antisepsis using alcohol-based hand rub reached 72.5%, which was lower than the 94.8% reported by Al Mutairi et al (25). The major determinants of the use of alcohol-based hand rubs are the cost and availability of these products (25). Masks are often worn to prevent transmission of infection via droplets in the community or healthcare settings.…”
Section: Discussionmentioning
confidence: 93%